Teaching Australian literature in a class about literatures of social reform - Henningsgaard, Per (American Association of Australian Literary Studies, 2014)
This article considers the theoretical and political implications of teaching Sally Morgan's My Place to American university students alongside Upton Sinclair's The Jungle and Harriet Beecher Stowe's Uncle Tom's Cabin.